Veiled landscapes: Analyzing the Aucaypata esplanade during the Inca Empire in Cusco - Takano Valdivia, Karen (2025)
The Esplanade of Aucaypata, located in the main square of Cusco, played a pivotal role as the central physical focal point of the Inca Empire, with intricate landscapes hidden beneath the surface. The research endeavors to deepen our comprehension of the pre-Columbian urban landscape by amalgamating insights from diverse disciplines such as archaeology, architecture, anthropology, and history. Employing a historiographic methodology grounded in qualitative analysis, the study operates at an exploratory and descriptive level.The veiled landscapes are divided into two: (a) extended landscape, territorial scale, and (b) transported landscape, within the limits of Aucaypata, temporary displacements of substrates and trees, and imagined or unusual landscapes.What was found suggests that the conception of the Inca landscape was more than a series of physical operations with aesthetic or productive purposes. The symbolic and sacred character of the interventions in the territory shows highly complex relationships.